Determinants of Implied Volatility Function on the Nifty Index Options Market: Evidence from India - Sanjay Sehgal,; N. Vijayakumar, (Asian Academy of Management Journal of Accounting and Finance, 2008)
In this paper, we examine two important propositions for the Indian options market: (1) the relationship between implied volatility and moneyness referred to as volatility smile and (2) the potential determinants of the smile asymmetry. We use daily data for the S&P CNX Nifty index call and put options and the underlying market index for the calendar years 2004 and 2005. We find that the volatility functions exhibit a positive slope in the Indian context using alternative measures of moneyness, thus confirming the consistency of our findings. Our evidence on smile asymmetry is in contrast with findings for mature markets, which exhibit negative asymmetry profiles in general. This may be owing to differences in investors' behaviour and market microstructure between mature and emerging markets. We also show that historical volatility and time to expiration are the potential determinants of smile asymmetry in India, as is the case with international evidence. We feel that a strong theoretical foundation should be provided for this observable empirical phenomenon.